Economic Analysis of Crypto Asset Regulation in Indonesia: Market Impact, Investor Behavior and Islamic Economic Perspective - Nanda Nur Sofyana (PT. Radja Intercontinental Publishing, 2026)
The transfer of crypto asset regulatory authority from Bappebti to the Financial Services Authority (OJK) in 2025 represents a policy transformation with significant economic consequences for Indonesia's digital financial market. This article presents a narrative literature review analyzing three economic dimensions of this regulatory change: (1) the impact of regulation on market dynamics and crypto asset price volatility; (2) the response and behavior of crypto investors in Indonesia amidst the changing regulatory landscape; and (3) the implications of regulation from an Islamic economic perspective based on the 2021 Ijtima Ulama. The review results indicate that: first, regulations that increase legal certainty have the potential to suppress short-term volatility while encouraging long-term institutional adoption, although empirical evidence suggests that the announcement of regulations was initially responded negatively by market players; second, the growth of Indonesian crypto investors, reaching more than 21 million by 2024, is driven by digital financial literacy, risk perception, and speculative motives, which require a policy approach based on economic education; Third, the 2021 Ijtima Ulama fatwa places crypto assets in a conditional position from an Islamic economic perspective, namely, they are forbidden as a medium of exchange but offer opportunities as conditional investment assets. Therefore, OJK regulations need to accommodate the evolving needs of Muslim investors. This article identifies a research gap in the form of a lack of empirical studies on the macroeconomic impact of crypto regulations in Indonesia and the need for a regulatory model that integrates Islamic economic principles.